2013
DOI: 10.1002/hep.26686
|View full text |Cite
|
Sign up to set email alerts
|

No detectable resistance to tenofovir disoproxil fumarate after 6 years of therapy in patients with chronic hepatitis B

Abstract: One major challenge in the treatment of chronic hepatitis B is to maintain long-term viral suppression without promoting the selection of drug-resistant mutations. We analyzed data from 347 hepatitis B e antigen-negative and 238 hepatitis B e antigenpositive patients receiving tenofovir disoproxil fumarate (TDF) in an open-label, longterm extension of two phase 3 studies. To date, resistance analyses have been completed for patients receiving up to 288 weeks (6 years) of TDF. Population sequencing of hepatitis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
179
0
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(201 citation statements)
references
References 26 publications
16
179
0
6
Order By: Relevance
“…Subsequent studies have confirmed these findings by concurrently measuring virological breakthrough and non-adherence [18,20,[22][23][24], but none provided a consistent definition for non-adherence that is evidence-based. One of the most challenging issues in the field of medication adherence research is the use of varied definitions and arbitrary cut-off points to define adherence to therapies.…”
Section: Factors Associated With Hepatitis B Virus Virological Breaktmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequent studies have confirmed these findings by concurrently measuring virological breakthrough and non-adherence [18,20,[22][23][24], but none provided a consistent definition for non-adherence that is evidence-based. One of the most challenging issues in the field of medication adherence research is the use of varied definitions and arbitrary cut-off points to define adherence to therapies.…”
Section: Factors Associated With Hepatitis B Virus Virological Breaktmentioning
confidence: 99%
“…anti-viral therapies, recent reports have acknowledged the relationship between nonadherence and virological breakthrough [18,22,23,38]. provides key information to be delivered during patient education and adherence counselling.…”
Section: Relationship Between Days Of Medication Missed and Virologicmentioning
confidence: 99%
See 1 more Smart Citation
“…ADV resistance rate is approximately 30% after a 5-year treatment, with even higher rates in NAs experienced patients (55). ETV and TDF are the drugs with a higher genetic barrier to resistance, reporting 1.2% of resistant mutation after 5 years of treatment for ETV, while no resistance has been previously been reported after 6 years of treatment for TDF (56,57).…”
Section: Resistance Ratementioning
confidence: 99%
“…A 5-year study showed that tenofovir achieved a higher HBsAg-negative conversion rate compared to other NUCs [91] . A recent report with 288 wk of follow up suggested that no apparent resistance mutations were observed [94] . For decompensated cirrhosis, the combination of tenofovir with emtricitabine was reported to achieve positive results [89] .…”
Section: Tenofovir Disoproxil Fumarate (Tenofovir)mentioning
confidence: 99%